KULTUROWE PRZETRWANIE INDIAN YAQUI NA POGRANICZU MEKSYKAŃSKO-AMERYKAŃSKIM W POWIEŚCI LESLIE MARMON SILKO ALMANAC OF THE DEAD - Bańka, Ewelina (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article analyzes the yaqui indians’ strategies of maintaining cultural integrity and identity in the U.S.-Mexico borderland portrayed in leslie Marmon Silko’s novel, Almanac of the Dead. drawing on the ancient mythologies throughout the Western hemisphere, Silko creates a complex narrative about the decline of the Western world in the Americas, accompanied by the eventual retaking of the lands by indigenous people. The pan-tribal revolution launched against the euro-American power aims at restoring tribal values, strengthening people’s bond with the land, and affirming the cultural continuity of indigenous nations. While the U.S.-Mexico borderland constitutes the core arena of the activities described in the novel, the international border becomes Silko’s key symbol to represent the euro-American domination which, according to the ancient prophecies inscribed in the novel, is coming to an end in the Americas. Silko’s portrayal of the yaqui indian community’s strategies of defying Mexican and U.S. territorial land claims points not only to the yaquis’ continuous struggle for their cultural integrity as a people but also stresses the dynamic and adaptive character of yaqui identity. eventually, the yaqui resistance against the euro-American geopolitical and cultural domination can be seen as a symbolic struggle of all indigenous people for their cultural continuity across the Americas.